Viscosimetric behaviour of n-alkanols with triethylene glycol monomethyl ether at different temperatures - Aznarez, Silvia (2008)
The thermodynamic functions of activation for viscous flow have been evaluated from the dynamic viscosity values of binary mixtures considering Eyring's transition state theory. Kinematic viscosities and densities of binary mixtures containing triethylene glycol monomethyl ether + (2-propanol or 2-butanol or 2-pentanol) over the whole mole fraction range of triethylene glycol monomethyl ether, at four different temperatures and atmospheric pressure were determined. Viscosity deviations and excess Gibbs energies of activation for viscous flow were calculated. All the values of viscosity deviations are negative, at all temperatures. The molar enthalpy of activation for viscous flow and molar entropy of activation for viscous flow functions were obtained. These functions with concentration of the triethylene glycol monomethyl ether show a minimum. These mixtures show a similar behaviour to that of the hydrocarbon-alkanol mixtures. The Grunberg-Nissan and Katti-Chaudrhi parameters were calculated and viscosity data were analyzed on the basis of their treatment. © 2007 Elsevier B.V. All rights reserved.